The Relationship of Satiseaction Level and Content of Job Satisfaction Questionnaire Items to Item Sensitivity - Giles, William F.; Feild, Hubert S. (Academy of Management Journal, 1978)
In this article the authors discuss research they conducted that examined the relationship between item sensitivity on job satisfaction questionnaires and the respondent's level of job satisfaction. They note that respondents would be more likely to falsely answer questions that they believe would have negative consequences if their identity were revealed. Their aim is to discover what items can be considered to be of high and low sensitivity. They found that low sensitivity items related to impersonal matters and working conditions while high sensitivity items related to supervision, competency of colleagues and overall job satisfaction.